2000
DOI: 10.1002/1531-8249(200005)47:5<583::aid-ana5>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Fumaric aciduria: Clinical and imaging features

Abstract: Fumaric aciduria (fumaric acidemia, fumarase deficiency) is a rare inborn error of metabolism caused by deficient activity of fumarate hydratase, one of the constituent enzymes of the Krebs tricarboxylic acid cycle. We describe the clinical and imaging features of this disease arising from a consanguineous pedigree in 8 patients in the southwestern United States. Thirteen patients have been previously described in the medical literature. Our patients presented with an early infantile encephalopathy with profou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(43 citation statements)
references
References 20 publications
0
41
0
2
Order By: Relevance
“…It must be observed that in disorders with abnormalities in cell energy production, dysmorphic features may occur. However, the underlying mechanism in fumaric aciduria is unknown (Kerrigan et al 2000;Peters and Kahler 2003).…”
Section: Case Reportmentioning
confidence: 99%
See 2 more Smart Citations
“…It must be observed that in disorders with abnormalities in cell energy production, dysmorphic features may occur. However, the underlying mechanism in fumaric aciduria is unknown (Kerrigan et al 2000;Peters and Kahler 2003).…”
Section: Case Reportmentioning
confidence: 99%
“…In general, the main fetal anomalies associated with polyhydramnios are a consequence of disorders that affect gastrointestinal, musculoskeletal and the central nervous system (CNS) (Kyle et al 1997). Angulation of the frontal horns and optic nerve hypoplasia/pallor were described in a consanguineous family that had eight affected members; these features are unique in study group (Kerrigan et al 2000). By the time of their respective reports, ten patients had died early (28%), seven of them being younger than 1 year, such as the case here reported.…”
Section: S-malatementioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in fumarase have been implicated in a variety of human diseases, including progressive encephalopathy, fumaric aciduria, hereditary leiomyomatosis and renal cell cancer (Kerrigan et al, 2000;Yang et al, 2013;Whelan et al, 1983). Despite its remarkable importance, the only structural study presently available regarding the clinical relevance of human fumarase (HsFH) was performed on the Escherichia coli FumC homologue, which shares 60% identity with the human enzyme (Esté vez et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…We report a patient with mild phenotype and two novel mutations, at least one being related to familial tumors. (Kerrigan JF et al 2000). Twelve autosomal recessive mutations in the FH gene associated with FH deficiency have been reported so far.…”
Section: Discussionmentioning
confidence: 99%